Advanced Skin Antisepsis: Application of UVA-Cleavable Hydroxyethyl Starch Nanocapsules for Improved Eradication of Hair Follicle-Associated Microorganisms - Loris Busch; Anna Maria Hanuschik; Yuri Avlasevich; Katrin Darm; Elisa F. Hochheiser; Christian Kohler; Evgeny A. Idelevich; Karsten Becker; Peter Rotsch; Katharina Landfester; Maxim E. Darvin; Martina C. Meinke; et al. (MDPI AG, 2023)
Hair follicles constitute important drug delivery targets for skin antisepsis since they contain ≈25% of the skin microbiome. Nanoparticles are known to penetrate deeply into hair follicles. By massaging the skin, the follicular penetration process is enhanced based on a ratchet effect. Subsequently, an intrafollicular drug release can be initiated by various trigger mechanisms. Here, we present novel ultraviolet A (UVA)-responsive nanocapsules (NCs) with a size between 400 and 600 nm containing hydroxyethyl starch (HES) functionalized by an o-nitrobenzyl linker. A phase transfer into phosphate-buffered saline (PBS) and ethanol was carried out, during which an aggregation of the particles was observed by means of dynamic light scattering (DLS). The highest stabilization for the target medium ethanol as well as UVA-dependent release of ethanol from the HES-NCs was achieved by adding 0.1% betaine monohydrate. Furthermore, sufficient cytocompatibility of the HES-NCs was demonstrated. On ex vivo porcine ear skin, a strong UVA-induced release of the model drug sulforhodamine 101 (SR101) could be demonstrated after application of the NCs in cyclohexane using laser scanning microscopy. In a final experiment, a microbial reduction comparable to that of an ethanol control was demonstrated on ex vivo porcine ear skin using a novel UVA-LED lamp for triggering the release of ethanol from HES-NCs. Our study provides first indications that an advanced skin antisepsis based on the eradication of intrafollicular microorganisms could be achieved by the topical application of UVA-responsive NCs.